Relationship Between Body Size and Skeletal Age with Muscle Damage in Young Soccer Players - Ramos-Silva, Luiz Fernando; Costa, Julio Cesar; Borges, Paulo Henrique; Moura, Felipe A; Deminice, Rafael; de Oliveira, Donizete Cícero Xavier; Osiecki, Raul; Vaz Ronque, Enio Ricardo (International Journal of Sports Medicine, 2023)
This study verified the relationship between body size and skeletal age (SA) with the behavior of blood markers of muscle damage and delayed onset muscle soreness (DOMS) after a soccer match in the U-13 and U-15 categories. The sample consisted of 28 soccer players in the U-13 and 16 in the U-15 categories. Creatine kinase (CK), lactate dehydrogenase (LDH), and DOMS were evaluated up to 72 h after the match. Muscle damage was elevated at 0 h in U-13, and from 0 h to 24 h in U-15. DOMS increased from 0 h to 72 h in U-13 and from 0 h to 48 h in U-15. Significant associations of SA and fat-free mass (FFM) with muscle damage markers and DOMS were observed only in U-13, specifically at time 0 h, when SA explained 56% of CK and 48% of DOMS and FFM explained 48% of DOMS. We concluded that in the U-13 category, higher SA is significantly associated with muscle damage markers, and increase in FFM is associated with muscle damage markers and DOMS. Furthermore, U-13 players need 24 h to recover pre-match muscle damage markers and more than 72 h to recover DOMS. In contrast, the U-15 category needs 48 h to recover muscle damage markers and 72 h to recover DOMS.
Keywords: football; growth; adolescents; creatine kinase; lactate dehydrogenase, fatigue